Peluang dan Tantangan Sektor Jasa Konstruksi Indonesia dalam AFAS - Muhammad Fawaiq; Ranni Resnia (Journal of World Trade Studies, 2012)
The role of trade in services becomes more important as its contribution to ASEAN countriesi GDP achieved 40 70% last year. Gradual liberalisation in service sector until 2015 creating opportunities in both outward and inward investments. This study aims to map commitment position of Indonesian trade in construction services on AFAS, to analyse conformity of Indonesian cornmitment on AFAS with existing related regulations, and to estimate performance of construction services firms. Methods used in this paper are Hoekman Index, descriptive analysis, and ROA and ROE to estimate construction firms performance toward competition. The results show that Indonesian'commitment on AFAS is at the same level as Malaysia and Cambodia, however lower than commitments of Singapore, Laos, Mycmmar, Thailand, and Vietnam, but it is higher than Brunei Darussalaam and the Philipines. Nevertheless, the study shows that Indonesian commitment is in accordance with the existing regulations. Lastly, the performance of consruction firms has been increasing since 2008 to 2011.